Museums and science communication concerning paleontology - Kellner, Alexander Wilhelm Armin (Anuário do Instituto de Geociências, 2005)
Museums are generally regarded as having high potential for science communication. In Brazil, however, those institutions are still far away from accomplishing this mission, particularly regarding paleontology. Here we discuss several aspects regarding science communication and museums. The three main activities associated to museums are research, repositories of collections and exhibitions. The collections of the Brazilian museums and the exhibits tend to be poor when compared with similar European and North American institutions, causing a distance between museum and society. Among the attempts of changing this picture, the Museu Nacional/UFRJ, in collaboration with the Museu de Ciência da Terra (DNPM), has organized in 1999 the temporary exhibition THE TIME OF THE DINOSAURS, which turned out to be the most visited exposition regarding fossils organized in the country so far. Among the several benefits of this exhibit was to increase the interest of the population regarding paleontology. This experience has shown that the museum must interact more strongly with the society in order to fully develop its potential of science communication.